Use of Negative Pressure Wound Therapy in Pedicled Flaps can Improve Graft Integration and Minimize Complications - Suarez, Maria A.; Latorre, Luis F.; Quintero, Jorge I.; Hand Microsurgery Research Group (Journal of Reconstructive Microsurgery Open, 2024)
Negative pressure wound therapy (NPWT) has been used in the treatment of open fractures to improve local wound treatment, to allow skin integration when skin grafting is needed. During the last decade, the use of this device contributes to decreasing the venous congestion in microsurgical procedures in free flaps and finger replantation. The negative pressure increases the vascularization and decreases the edema, allowing the integration of tissue. Nine patients were included in this protocol. These patients had an open wound, and primary healing was not an option. Therefore, reconstructive surgery was needed. One female and eight male patients were included. Five reconstructive surgeries were performed in the lower limb and four in the upper limb due to an open fracture, skin defect secondary to infection, avulsion injury of the upper limb, and electric burn. Following the reconstructive procedure, NPWT was applied immediately peripheral to the pedicled flap. Our protocol indicates that the suction was placed for 5 days, set at continuous pressure of −100 mm Hg. At the end of the treatment, no complications were observed, and full integration of the flap was achieved. NPWT avoids local complications such as hematoma, shearing forces, and infection.
Keywords: NPWT; pedicled flaps; healing